Changes and Challenges in Crime and Criminal Justice After Disaster. (September 2015) - Frailing, Kelly; Harper, Dee Wood; Serpas, Ronal
While prosocial behavior is widely observable after disaster, there is undeniable evidence that antisocial behavior also occurs in the immediate and longer term aftermath of disaster. We begin by examining the crime that occurred in New Orleans in the immediate wake of Katrina and the circumstances that facilitated it. We also take a longer term look at one of New Orleans' most intractable crime problems, that of murder. We explore Katrina's direct and indirect effect on murder rates in New Orleans, including innovative law enforcement responses to this crime. We conclude with a discussion of policies and practices relevant to reducing crime in the immediate and longer term wake of disaster that incorporate law enforcement and other initiatives.